Abon Tongkol: Modern Product Innovation with Economic Value as an Alternative for Healthy Food to Prevent Stunting in Malaka Village - Sari Novida; Aena Mardiah; Vegalyra; Pandawani; Wahyu Udayani; Yuria Mendra (Unram Journal of Community Service, 2026)
Malaka Village has extraordinary natural potential in both the agricultural and fisheries sectors. One of the agricultural potentials of Malacca village is producing nuts. The potential fishery is producing tuna. Apart from its extraordinary natural wealth, Malacca village has an important problem to overcome, namely the high rate of stunting. The village government has made many efforts to reduce stunting rates over the last 5 years, one of which is providing nutrition for pregnant women and children. Shredded Tongkol is an alternative protein that can be consumed by children who are diagnosed with stunting, because the nutritional content in it is complex. The objectives of this service are: (1) providing information on nutritious food for pregnant women, children and teenagers; (2) training in making more innovative shredded cob; (3) Training on packaging for shredded cob products to produce economic value which has an impact on increasing income. The methods used are socialization and training, application of technology, evaluation and assistance in future sustainability. Training on making shredded cob and packaging training has been carried out and these activities have increased the knowledge and skills of partners. It is hoped that in the future partners will be able to produce abon cob typical of Malaka Village, with the aim of increasing community income.